Potential of Uncaria Gambir Extract Against Glucosyltransferase Enzyme: A Narrative Review - Dewi, Siti Rusdiana Puspa; Nabiilah, Zata Yumni (Interdental Jurnal Kedokteran Gigi (IJKG), 2026)
Introduction: Glucosyltransferase (Gtf) enzyme is an enzyme produced by Streptococcus mutans (S. mutans) bacteria that plays an important role in the process of attachment and virulence of bacterial colonies on the tooth surface. Gambier plants (Uncaria gambir (Roxb.)) have the main content of catechins and tannins that can prevent the formation of extracellular glucans that bind S. mutans bacteria on the tooth surface. The purpose of this narrative review is to determine the potential of gambir extract on Gtf enzymes produced by S. mutans. This article is a narrative review, with databases sourced from PubMed, Wiley Online Library, Cochrane, and Science Direct. Review: A total of 251 articles were identified, and 6 journals were filtered that met the inclusion and exclusion criteria for analysis. Catechins and tannins contained in gambir have inhibitory action against Gtfs, so that the activity of EPS synthesis by S. mutans is blocked. Inhibition of Gtf by catechins does not interfere with the existence of microbes in the oral environment. Therefore, the ability of catechins extracted from gambir plants is able to inhibit the Gtf enzyme selectively, and is developed as a material that can prevent the formation of dental caries. Conclusion: Gambier extract has the potential to inhibit the formation of Gtf enzymes.